The medial femoral condyle free flap: An excellent option for difficult cases: case series. (June 2020) - Quintero, Jorge I; Childs, Dylan; Moreno, Rodrigo
The use of the medial femoral condyle free flap is a versatile option for the treatment of upper extremity non unions and reconstructive procedures associated with bone loss or osteonecrosis. The benefit of this type of flap is the viability of the bone which favors primary ossification and increases bone density. Vascularized free bone flaps are especially useful for the treatment of recalcitrant nonunions, or nonunions that have failed three or more treatments to obtain consolidation. We present a case series of three patients treated with medial femoral condyle free flap for reconstruction of the upper extremity of different etiologies at the level of the distal humerus, distal radius and distal phalanx of the thumb.